Aplikasi Edible Coating Tepung Tapioka Dengan Oleoresin Daun Kemangi untuk Memperpanjang Umur Simpan Buah Jambu Air Cincalo (Syzygium samarangense [Blume] Merril & L.M. Perry): Aplikasi Edible Coating Tepung Tapioka Dengan Oleoresin Daun Kemangi untuk Memperpanjang Umur Simpan Buah Jambu Air Cincalo (Syzygium samarangense [Blume] Merril & L.M. Perry) - Wiwik Sumanti; Riwan Kusmiadi; Rion Apriyadi (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2020)
Cincalo wax apple has non-climacteric respiration activity with high water content, so that not exactly post-harvest handling will trigger fungal growth. This study aims to determine the effect of edible coating from basil leaf oleoresin and determine the best concentration to extend the storage duration of cincalo wax apple. The study used a single completely randomized design (CRD), there were 4 treatments which were the types of basil leaf oleoresin concentrations consisting of K0 (without the addition of oleoresin), K1 (0,3% oleoresin), K2 (0,6% oleoresin) and K3 (0,9% oleoresin) with 3 replications. The variables observed were weight loss, total dissolved solids, total fruit acids, vitamin C content and organoleptic index. The results showed that the treatment of basil leaf oleoresin concentration had no significant effect on the observed variables, including weight loss, total dissolved solids, total fruit acid, and vitamin C content. All treatments with the addition of oleoresin or without the addition of basil leaf oleoresin tend to have the same results on cincalo wax apple.